The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31557/apjcp.2020.21.6.1731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hip Prosthesis on Photon Beam Characteristics in Radiological Physics

Abstract: Introduction: Aim of study is to investigate the effect of hip prosthesis on 6 and 15 MV photon beam energies. Materials and Methods: Prosthesis was kept at the level of tray position. The measurements were done on Varian Clinac-iX linac. Customized prosthesis, termed as Prosthetic Metal Implant (PMI) was made up of wrought austenitic stainless steel rod and covered with paraffin-wax. ‘Standard prosthesis’ was made up of wrought titanium alloy. The dose profiles were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There were many publications on the planning of hip implant patients. [ 4 16 32 33 ] For the hip prosthesis patients, the optimization strategies used in our study were less explored. We used seven fields for IMRT plans and two arcs for the VMAT plans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were many publications on the planning of hip implant patients. [ 4 16 32 33 ] For the hip prosthesis patients, the optimization strategies used in our study were less explored. We used seven fields for IMRT plans and two arcs for the VMAT plans.…”
Section: Discussionmentioning
confidence: 99%
“…The radiotherapy (RT) starts with the simulation of a patient and computed tomography (CT) images are standard 3-dimensional (3D) imaging procedure for RT patients. The presence of metal in the treatment region changes the attenuation profiles of photon beams passing through it[ 4 ] because of these profiles and scattered photons different artifacts are produced in the CT images. [ 5 6 7 ] A few artifacts seen during CT procedures are streaking, shading, rings, and distortions.…”
Section: Introductionmentioning
confidence: 99%
“…Stainless steel is widely used in bone fixation, cardiovascular systems, catheters, surgical instruments and dental crowns ( 30 ). Furthermore, Bhushan et al ( 27 ) studied the effect of stainless-steel hip prosthesis on radiation using a customized prosthesis containing wrought austenitic stainless steel. It was observed that for 6 MV of photon irradiation, at a depth of 10 cm below the prosthesis, with field sizes of 5x5, 10x10 and 20x20, the dose attenuation was 8.3, 7.4 and 7.5% when the prosthesis was present compared with in its absence.…”
Section: The Effect Of Different Kind Of Metal Implants On Dosagementioning
confidence: 99%
“…All these information are required for executing the dose computations with precision. Bhushan et al [5] reported that dose perturbation changes with a factor for different energies also. Patients had already completed the total course of treatment.…”
Section: Patient Selectionmentioning
confidence: 99%